Mismatch Developmental-HOTS Load pada Siswa Kelas 1 SD dan Dampaknya terhadap Prestasi Belajar - Novi Wibowo (CV. Lentera Literasi Indonesia, 2026)
This study aims to examine the appropriateness of higher order thinking skills (HOTS) assessment for Grade 1 elementary students and its impact on learning achievement from a cognitive developmental perspective. The research employed a qualitative approach using a descriptive case study conducted at SD Negeri 2 Parijatah Kulon. The participants consisted of 17 Grade 1 students and one classroom teacher. Data were collected through classroom observations, semi-structured interviews, and document analysis of HOTS-based assessment items. The findings indicate that most students experienced significant difficulties in understanding instructions and engaging in analytical and evaluative thinking required by HOTS items, resulting in learning achievement that did not accurately reflect their actual abilities. This study identifies a phenomenon termed Mismatch Developmental-HOTS Load, referring to the misalignment between the cognitive demands of HOTS questions and the developmental cognitive capacity of early-grade students. The novelty of this research lies in its conceptual contribution to educational psychology by emphasizing the importance of developmentally appropriate assessment. The study highlights the need for adaptive HOTS design aligned with children’s cognitive development to ensure valid, fair, and psychologically meaningful evaluation practices in early elementary education.